Exploring proxies of net interest margin : a comparative analysis of asian developed and emerging banking sector - Susanti, Susy; Budhidharma, Valentino (Enrichment : Journal of Management, 2024)
This study aims to explore the proxies of Net Interest Margin (NIM) across banks in both developed and emerging Asian countries. The research spans from the first quarter of 2012 to the fourth quarter of 2023 and involves countries including Japan, Hong Kong, Singapore (developed) and Indonesia, Malaysia, and the Philippines (emerging). The estimation method is panel data, using fixed effects panel data regression to accommodate variations over time and across entities. The result showed that in developed countries, banks benefit from maintaining a low Cost-to-Income Ratio (CIR) and managing provisions effectively, enhancing operational efficiency and profitability. Challenges such as the negative impact of larger asset sizes and economic shocks like COVID-19 necessitate innovative and adaptive strategies. While in emerging countries, effective management of provisions, along with adapting to GDP growth and inflation impacts, is crucial. The negative effects of COVID-19 and inflation on Net Interest Margin (NIM) highlight the importance of resilient strategies that enhance efficiency and adapt to economic changes. For both regions, prioritizing effective provisions management and adapting to economic fluctuations are key to sustaining profitability